Study Guide to accompany international economics : - Krugman, Paul R. (Addison Wesley, 2003)
This Study Guide designed to enhance your understanding of important ideas in international economics. As a supplement to the text, it provides you with an opportunity for text is represented by a coresponding chapter in the Study Guide. The individual chapter terms, a set of multi-part review questions, and answers to odd-numbered problems from the textbook. Answers to all Study Guide Review Questions are provided at the back of the Study Guide.